Bond behavior of grouted spiral and splice connection under direct axial and flexural pullout load - Aldin Hosseini, Seyed Jamal (2015)
The conventional grouted connections with corrugated aluminium sleeves have been used widely in precast concrete construction. The main problem of the conventional grouted sleeve connections is the need for long embedded lengths reinforcement rebars to achieve full continuity. There is a tendency for the long rebars to touch the sleeve wall and subsequently preventing penetration of grout around the rebar. Since the grout inside the sleeve cannot be inspected after installation, there is doubt that the main rebar is fully bonded. This study proposed a grouted spiral connection which can overcome the use of long embedded length of connected rebars. The main objective of this study was to investigate the effect of spiral confinement on the bond stress-slip relationship. The experimental program was carried out in two phases, Phase I and Phase II. In Phase I, a total of thirty-six spiral connections were subjected to increasing direct axial pullout loads. Then, in Phase II, a total of twelve beams comprising spiral connections were subjected to flexural pullout loads. Parameters considered in this study were pitch distance and diameter of spiral connections. The experimental results showed that the use of smaller pitch distance and spiral diameter resulted in higher bond strength. However, the spiral diameter had more dominant confinement effect such that it increased the bond strength of direct and flexural pullout tests very dramatically by 34.5% and 40%, respectively. In addition, lower bond strength from the beam tests was reported as compared to the axial pullout tests. The bond strengths obtained from the flexural pullout tests were within the range of 0.74 to 0.79 times the bond strengths of the axial pullout tests. Finally, analytical equations were proposed to express the bond stress-slip relationship and bond strength of the grouted spiral connection.